Efficient and Robust Metallic Nanowire Foams for Deep Submicrometer Particulate Filtration - Malloy, James; Quintana, Alberto; Jensen, Christopher J; Liu, Kai (Nano letters, 2021)
The ongoing COVID-19 pandemic highlights the severe health risks posed by deep submicrometer-sized airborne viruses and particulates in the spread of infectious diseases. There is an urgent need for the development of efficient, durable, and reusable filters for this size range. Here we report the realization of efficient particulate filters using nanowire-based low-density metal foams which combine extremely large surface areas with excellent mechanical properties. The metal foams exhibit outstanding filtration efficiencies (>96.6%) in the PM0.3 regime, with the potential for further improvement. Their mechanical stability, light weight, chemical and radiation resistance, ease of cleaning and reuse, and recyclability further make such metal foams promising filters for combating COVID-19 and other types of airborne particulates.